2018
DOI: 10.29252/jhsme.5.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Observance of the Codes of Professional Ethics in Clinical Care: Perspectives of Nurses and Midwifery of Hospitals Affiliated with Qom University of Medical Sciences in 2016

Abstract: Background and Objectives: The observance of professional ethics is one of the most important expectations from health care team whose application has a tremendous effect on treatment course. The aim of this study was to investigate barriers to observance of the codes of professional ethics in clinical settings from the perspectives of nurses and midwifery in hospitals affiliated with Qom University of Medical Sciences in 2016. Methods: This descriptive cross-sectional study was conducted with 246 nurses and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Research findings of a previous survey on the difficulties to psychiatric treatment, highlighted that negative experience with the provider will cause the users to stop the treatment that they are receiving or select another health service for the care of people with mental illness. These problems can result in decreased patients" care management (45) .…”
Section: Resultsmentioning
confidence: 99%
“…Research findings of a previous survey on the difficulties to psychiatric treatment, highlighted that negative experience with the provider will cause the users to stop the treatment that they are receiving or select another health service for the care of people with mental illness. These problems can result in decreased patients" care management (45) .…”
Section: Resultsmentioning
confidence: 99%
“…Also, in another study, a positive association was observed between nurses' shiftwork and the quality of professional ethics, to the extent that nurses working on a morning shift have better ethical performance than nurses in night and evening shifts. 21 This issue can be explained by two possible reasons including the presence of nurse managers in the morning shift in the hospital and high work experience of the morning shift staff. 22,23 Nursing managers are responsible for overseeing the nurses’ observance of the ethical codes and as a part of their supervisory responsibilities have a critical perspective of nurses ethical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, nurses consider inhibitors and facilitators to be involved in compliance with professional ethics [ 3 ]. In their view, lack of ethics retraining courses, inappropriate communication between nurses and head nurses, lack of suitable equipment are inhibitors [ 7 ], and individual beliefs and the promotion of ethical knowledge are facilitators of compliance with PES [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Esmaelzadeh et al, “the ability of nurses to make ethical decision” as a facilitating factor in compliance with PES [ 9 ], and in the study s of Khaki et al, “inability of nurses to make ethical decisions” as an inhibiting factor in compliance with PES from the point of view of nurses have been reported [ 7 ]. At first glance, it seems that the presence of a factor in the observance of PES as a significant facilitator can indicate the importance of its absence as an inhibitor.…”
Section: Introductionmentioning
confidence: 99%